Evaluation of corrosion inhibition to Pteridium aquilinum extract via the methods of electrochemistry experiment. (13th November 2019) - Wang, Qihui; Wang, Qianyu; Ni, Zihui; Bao, Hebin; Li, Xueming
Abstract: Plant extracts are expected to be used as eco–friendly corrosion inhibitors due to their advantages of natural degradation and regeneration. In this study, potentiodynamic polarization and electrochemical impedance spectroscopy were used to evaluate the inhibition performance of Pteridium aquilinum (L.) Kuhn ( Pteridium aquilinum) extract on carbon steel in hydrochloric acid. The temperature adaptability of Pteridium aquilinum extract in the range of 25 °C–45 °C was investigated by scanning electron microscope. The functional groups in Pteridium aquilinum extracts were analyzed by Fourier transformed infrared spectroscopy. The results showed that the Pteridium aquilinum extract followed the Langmuir adsorption isotherm and acts as mixed–type corrosion inhibitor. Inhibition efficiency up to 96.9% has been achieved for 500 ppm Pteridium aquilinum extract at 25 °C. This study provides an important and useful reference for the research and utilization of plant extracts as corrosion inhibitors.